2022
DOI: 10.1128/jvi.00197-22
|View full text |Cite
|
Sign up to set email alerts
|

RetS Regulates Phage Infection in Pseudomonas aeruginosa via Modulating the GacS/GacA Two-Component System

Abstract: Our knowledge on the molecular mechanisms behind bacterium-phage interactions remains limited. Our study reported that the complex multisensing regulatory networks RetS-GacS/GacA of Pseudomonas aeruginosa PAO1 play key roles in controlling phage infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It has been reported that the twitching motility of P. aeruginosa depends on the integrity of the T4P (Type IV pilus) ( 19 , 20 ). Both phages vB_Pae_QDWS and vB_Pae_W3 could recognize T4P as their receptor sites ( 21 ). To investigate whether the alteration in the T4P receptor affects antiphage infection of PAO1-R1, we performed an adsorption assay.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the twitching motility of P. aeruginosa depends on the integrity of the T4P (Type IV pilus) ( 19 , 20 ). Both phages vB_Pae_QDWS and vB_Pae_W3 could recognize T4P as their receptor sites ( 21 ). To investigate whether the alteration in the T4P receptor affects antiphage infection of PAO1-R1, we performed an adsorption assay.…”
Section: Resultsmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) has evaluated phages and concluded that they are safe for both consumers and the environment, although each phage or phage cocktail intended for use in food must be assessed on a case-by-case basis ( Ricci et al., 2017 ; Rendueles et al., 2022 ). However, phage therapy can be complicated by the ability of bacteria to defend against phage attacks through various antiviral mechanisms, including spontaneous mutations, DNA restriction-modification, abortive infection systems, and the CRISPR-Cas adaptive immunity system ( Labrie et al., 2010 ; Dupuis et al., 2013 ; Monteiro et al., 2019 ; Xuan et al., 2022 ). Overcoming phage resistance is a key issue that urgently needs to be addressed to enhance the effectiveness of phage therapy.…”
Section: Introductionmentioning
confidence: 99%
“…While there is a research foundation for studying the functionality of PqsA protein and screening for inhibitors, its application in combating P. aeruginosa infections remains limited, and there is an urgent need to develop more effective treatment options such as phage therapy. However, phage therapy still faces the challenge of bacterial resistance to phage ( Labrie et al., 2010 ; Dupuis et al., 2013 ; Monteiro et al., 2019 ; Xuan et al., 2022 ). Therefore, we initially focus on exploring the potential application of PqsA protein in enhancing phage therapy and identifying essential gene targets for designing phage-antibacterial agents combination therapy to effectively combat P. aeruginosa infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation